Thymoquinone as a Natural Anti-Angiogenic Agent: Experimental Pharmacology insights into Schematic and Meta-Analysis of Ocular Neovascularization and Retinal Pathology - Soobia Pathan; Anaam Rehman; Syed Azhar Hussain Zaidi; Muhammad Imran Ali (Pakistan Journal of Medicine and Dentistry)
Background: Thymoquinone is seen to combat angiogenesis, reduce inflammation, and act as an antioxidant. This systematic review and meta-analysis aimed to assess the role of thymoquinone in angiogenesis, damage involving reactive oxygen species, and preservation of the retina in different preclinical models.